Hypoglycaemia, fear of hypoglycaemia and quality of life in children with Type 1 diabetes and their parents. Issue 9 (28th June 2013) - Johnson, S. R.; Cooper, M. N.; Davis, E. A.; Jones, T. W.
Abstract Aim To evaluate the association between fear of hypoglycaemia, episodes of hypoglycaemia and quality of life in children with Type 1 diabetes and their parents. Methods This was a cross‐sectional, population‐based study of 325 children with Type 1 diabetes and their parents. The children were aged 2–18 years. A total of 325 parents of the patients aged 2–18 years and 196 of the patients themselves (aged 8–18 years) completed questionnaires including the PedsQL Diabetes Module, the Hypoglycaemia Fear Survey and Clarke's hypoglycaemia awareness questionnaire. Data were compared with HbA1c results and the history of severe hypoglycaemia episodes. Results Parents with the highest levels of fear of hypoglycaemia reported that their children had a reduced quality of life (P < 0.001). Similarly children with the greatest fear also reported a reduced quality of life (P < 0.001); however a history of severe hypoglycaemia was not associated with the child's quality of life as perceived by the child or parent. Episodes of severe hypoglycaemia were associated with an increased fear of hypoglycaemia for the parents (P = 0.004) but not the children. Children in the highest fear quartile also had a higher HbA1c concentration compared with those in the lowest fear quartile [increase in HbA1c 7 mmol/mol (0.6%), P < 0.01]. Conclusions Fear of hypoglycaemia and not episodes of hypoglycaemia per se is associated with increased psychological burden for children with Type 1 diabetes. Interventions to reduce fear of hypoglycaemia in these families may improve their quality of life.